Pergeseran Wewenang Polri Menurut Undang-Undang Nomor 11 Tahun 2020 Tentang Cipta Kerja (Omnibus Law) Dalam Perspektif Tugas Kepolisian - Heru Pujo Handoko (Sekolah Tinggi Ilmu Kepolisian, 2022)
AbstractIndonesian National Police (INP) which has general authority and special police authority, in which article 75 of Law Number 11 of 2020 concerning Cipta Kerja. The Indonesian National Police is given the authority to grant business licenses and supervise business entities in the field of security services in accordance with statutory provisions in the business licensing. The provisions in the field of business licensing refer to Government Regulation Number 24 of 2018 concerning Electronically Integrated Business Licensing Services where the Police sector is one of the ones that are included in licensing regulatory reform in order to accelerate business services through the OSS (Online Single Submission) system. This authority contradicts the authority of the police universally and specifically in Indonesia where the Police are positioned as part of the economic, political and cultural sub-system. This authority can have an unprofessional impact on the Indonesian National Police and carry out the task of maintaining security and public order and law enforcement because it is contrary to the 1945 Constitution of the Republic of Indonesia. This research uses a normative research method, namely a process to find a rule of law, legal principles, as well as legal doctrines in order to answer the legal issues at hand. The research approach uses the legislation approach, historical approaches, theoretical approaches and philosophical approaches and conclusions are drawn deductively and inductively. Keywords : autority shift, Law No. 11 of 2020; Omnibus law, police duties AbstrakPolri memiliki kewenangan umum dan kewenangan kepolisian khusus, yang mana pasal 75 Undang-Undang Nomor 11 Tahun 2020 tentang Cipta Kerja. Kepolisian Negara Republik Indonesia diberikan kewenangan untuk memberikan izin usaha dan mengawasi badan usaha di bidang jasa pengamanan sesuai dengan ketentuan peraturan perundang-undangan dalam perizinan usaha. Ketentuan di bidang perizinan berusaha mengacu pada Peraturan Pemerintah Nomor 24 Tahun 2018 tentang Pelayanan Perizinan Berusaha Terintegrasi Secara Elektronik dimana pihak Kepolisian merupakan salah satu yang termasuk dalam reformasi regulasi perizinan dalam rangka percepatan pelayanan berusaha melalui OSS (Online Single Sistem pengajuan. Kewenangan tersebut bertentangan dengan kewenangan Polri secara universal dan khusus di Indonesia dimana Polri diposisikan sebagai bagian dari subsistem ekonomi, politik dan budaya. Kewenangan tersebut dapat berdampak tidak profesionalnya Polri dan mengemban tugas memelihara keamanan dan ketertiban masyarakat serta penegakan hukum karena bertentangan dengan UUD Negara Republik Indonesia Tahun 1945. Penelitian ini menggunakan metode penelitian normatif, yaitu suatu proses untuk menemukan suatu kaidah hukum, asas-asas hukum, serta doktrin-doktrin hukum guna menjawab permasalahan hukum yang dihadapi. Pendekatan penelitian menggunakan pendekatan perundang-undangan, pendekatan sejarah, pendekatan teoritis dan pendekatan filosofis serta ditarik kesimpulan secara deduktif dan induktif Kata kunci: pergeseran wewenang, UU No. 11 tahun 2020, UU Omnibus, tugas polisiTRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian // TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//